1997
DOI: 10.1172/jci119273
|View full text |Cite
|
Sign up to set email alerts
|

Fas ligand expression by astrocytoma in vivo: maintaining immune privilege in the brain?

Abstract: Astrocytomas are among the most common brain tumors that are usually fatal in their malignant form. They appear to progress without significant impedance from the immune system, despite the presence of intratumoral T cell infiltration. To date, this has been thought to be the result of T cell immunosuppression induced by astrocytoma-derived cytokines. Here, we propose that cell contact-mediated events also play a role, since we demonstrate the in vivo expression of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
211
1
3

Year Published

1998
1998
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(222 citation statements)
references
References 34 publications
7
211
1
3
Order By: Relevance
“…Glioma gene therapy with EGFR-transfected MSCs H Sato et al astrocytes. 28 Importantly, Fas expression was also undetectable on bulk EGFR-MSCs, excluding the possibility of the undetectable Fas expression on the 2G3 clone being a unique event associated with the cloning (data now shown). CD44, which has been known to mediate cell migration in various cell types including gliomas, 29,30 expressed on both primary and EGFRtransfected MSCs (Table 1).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Glioma gene therapy with EGFR-transfected MSCs H Sato et al astrocytes. 28 Importantly, Fas expression was also undetectable on bulk EGFR-MSCs, excluding the possibility of the undetectable Fas expression on the 2G3 clone being a unique event associated with the cloning (data now shown). CD44, which has been known to mediate cell migration in various cell types including gliomas, 29,30 expressed on both primary and EGFRtransfected MSCs (Table 1).…”
Section: Discussionmentioning
confidence: 76%
“…Based on our in vitro data, it is thought that this superior migratory response of EGFR-MSC over primary MSCs in vivo resulted from several biological events that were induced by EGFR gene insertion: (1) direct enhancement of migration by interaction of EGFR and its ligands as demonstrated in vitro; (2) resistance to FasL-induced apoptosis, because FasL is known to be expressed in both normal and neoplastic CNS tissues, 44 Glioma gene therapy with EGFR-transfected MSCs H Sato et al mechanisms including activation of PI3-K. 45 Akt provides a powerful survival signal in many systems, 46 and a recent study has demonstrated that Akt-engineered MSCs are more resistant to apoptosis and can enhance cardiac repair after transplantation into the ischemic rat heart. 47 Indeed, both bulk and cloned EGFR-MSCs were maintained as a cell line over 30 passages, whereas primary MSCs died after three to four passages within a span of a month after their harvesting from bone marrow.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Didenko et al (2002) demonstrated apoptotic T cells adjacent to Fas-L-expressing glioma cells and concluded that Fas-L expression by glioma cells activates the Fas pathway in infiltrating T cells and leads to T-cell apoptosis as a tumour defence mechanism. It seems unlikely that glioma-cell Fas-L expression is the dominant mechanism leading to T-cell apoptosis because Fas-L expression by glioma cells is by no means universal, either within individual tumours or amongst GBM as a group (Husain et al, 1998 andSaas et al, 1997). An alternative role for glioma cells in inducing T-cell apoptosis is that glioma cells act as non-professional antigen-presenting cells which present tumour antigens to T cells but do not provide a co-stimulatory signal.…”
Section: Discussionmentioning
confidence: 99%
“…37 For example, some glioblastoma cells express Fas ligand, which can cause the demise of fas-expressing T effector cells. 38 Glioblastoma cells can secrete both the latent and active form of transforming growth factor-, 39,40 a cytokine that inhibits proliferation of T cells and the effector functions of cytolytic T cells 41,42 and may thus contribute to the local suppression of immune functions within the CNS. 43 Glioma cells also secrete prostaglandin E2, which inhibits production of cytokines such as IFN-g and chemokines.…”
Section: Discussionmentioning
confidence: 99%